Uji Macam Benih Jamur Kuping Hitam (Auricularia Polytricha) Pada Komposisi Media Tanam - Sartono Joko Santoso (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACT The Research about Test of Speed Kinds Ear Mushroom Blackness (Auricularia Polytricha) on Media Plat Composition purpose was to know interaction between seed kinds and media plant composition to yield the ear mushroom blackness, have been done 1th November 2009until 9 February 2010 in mushroom house Gondangmanis village, Karangpandan district, Karanganyar regency. The research used Split Plot Desaign with elementary design of completely randomized design (CRD) consist of two treatments factors and 3 replications. There are Seed Kinds (M) consist of 4 kinds : M1 (Seed F0), M2 (Seed F1), M3 (Seed F2), M4 (Seed F3) and Media Plant Composition (K) consist of 3 kinds : K1 (Mixture 81 kg sawdust, 1 kg lime, 9 kg bran), K2 (Mixture 81 kg sawdust, 1 kg lime, 18 kg bran), K3 (Mixture 81 sawdust, 1 kg lime, 27 kg bran). The result of the research show that significant interraction between treatmen of seed kinds and media plant composition to diametree of fruit body, number of fruit body, and misture content M1K2 (Seed F1 and mixture 81 kg sawdust, 1 kg lime, 9 kg bran) poduce biggest number of fruit body namely 47. Key words : Ear Mushroom blackness, Media Plant Composition, Seed kinds.